HUBUNGAN STIMULASI ORANG TUA DENGAN PERKEMBANGAN ANAK USIA PRASEKOLAH SELAMA PANDEMI COVID - Rahmawati Maulidia; Lilla Maria; Ach Dafir Firdaus (Jurnal Kesehatan Mesencephalon, 2021)
The Covid-19 pandemic is the first and main health crisis that will occur in the world in 2020. This has led to policies from the Indonesian government, ranging from social distancing to changing physical distancing which has an impact on the online learning system. So the role of parents is very important in providing stimulation to children during online learning methods. The purpose of this study was to determine the relationship between parental stimulation and the development of preschool children during the Covid-19 pandemic. This study used a correlational analytic design with a cross-sectional approach in order to determine the relationship between early stimulation of parents and the development of preschool children during the Pandemic Covid-19 at Insan Permata Kindergarten, Malang City. The research sample consisted of all students of TK A and B TK Insan Permata 150 students. The sampling technique used total sampling. The independent variable was parental stimulation and the dependent variable was the development of preschool children. The instrument used was KPSP in google form which can be accessed used mobile online and the data is analyzed using SPSS Windows 7. The statistical results using the Spearman correlation test show that the p value= 0.203 (p value> 0.05), that means there is no relationship between parental stimulation and the development of preschool-aged children during the COVID-19 pandemic. The development of preschool children during the Pandemic Covid-19 was influenced by many factors so that a review of the correlation of one factor will be influenced by other factors. This research was expected to provide information to the school in making policies regarding the development of preschool children during the Pandemic Covid-19.Keywords: Stimulation, Parents, Development, Preschool Children, Pandemic Covid-19